Struktur Adhokrasi dan Matriks sebagai Solusi atas Kritik Birokrasi Di Lembaga Pendidikan - Endah Winarti (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2020)
Technology and globalization’s challenge, have demanded public service institutions, including educational institutions, continue to innovate and improve themselves in preserving with the times. On the other hand, the bureaucracy used today is less flexible and inefficient, so that it raises a lot of criticism, which shows the powerlessness of the bureaucracy to face that challenge. These criticisms present a new form: adhocracy and organizational matrix, which gives flexibility in the organizational structure. The article proposes to present solutions to overcome bureaucratic criticism by integrating adhocracy and matrix organization in educational institutions bureaucracy. The integration of the three forms of organizational structure is expected to make educational institutions flexible and efficient to be able to resist the challenges of the times.